Pengaruh Inokulasi Glomus etunicatum terhadap Biokimia Tanaman Tomat (Solanum lycopersicum L.) yang Ditanam pada Cekaman Garam - Salim, Mohamad Agus (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2023)
The presence of salt levels can cause an important abiotic stress today. Plants have a special strategy for dealing with salt stress. The purpose of this study was to determine the effect of the inoculation of the arbuscular mycorrhizal fungus Glomus etunicatum on several biochemical parameters of tomato (Solanum lycopersicum L.) grown under high levels of salt stress conditions. This study used a randomized block design with a factorial pattern and five replications. The first factor was with and without inoculation of the fungus G. etunicatum. The second factor was several concentrations of NaCl (0, 50, 100 and 200 mM). Parameters observed were levels of phosphorus, root infection, concentrations of chlorophyll and carotenoids, activity of antioxidant enzymes (superoxide dismutase and catalase) and levels of malondialdehyde at the end of observation (day 45). The results showed that the increasing concentration of NaCl, decreased the levels of phosphorus, the concentration of chlorophyll and carotenoids as well increased the activity of superoxide dismutase, catalase and malondialdehyde levels. While the G. etunicatum inoculation treatment had the opposite effect from the NaCl treatment. Likewise, the parameters of root infection decreased in tomato plants inoculated with G. etunicatum with increasing NaCl concentration treatment. The conclusion of this study is that the presence of arbuscular mycorrhizal fungi can reduce the negative impact of salt stress on tomato plants.